The Linkage Between The Dirac's Approach And The Hamilton-Jacobi Approach For Higher-Order Hamiltonian Constrained Systems (Journal of the College of Basic Education, 2024)
The linkage between the Dirac's approach and the Hamilton-Jacobi approach for higher order systems with constrained is studied. It is shown that the Dirac's approach his permanently agree with the Hamilton-Jacobi approach. The integrability conditions in the Hamilton-Jacobi approach hare equivalent of consistency conditions in the Dirac's approach.